Measurement of neuronal activity in a macaque monkey in response to animate images using near-infrared spectroscopy - Wakita, Masumi; Shibasaki, Masahiro; Ishizuka, Takashi; Schnackenberg, Joerg; Fujiwara, Michiyuki; Masataka, Nobuo (Frontiers in Behavioral Neuroscience, 2010)
Near-infrared spectroscopy (NIRS) has been used extensively for functional neuroimaging over the past decade, in part because it is considered a powerful tool for investigating brain function in human infants and young children, for whom other neuroimaging techniques are not suitable. In particular, several studies have measured hemodynamic responses in the occipital region in infants upon exposure to visual stimuli. In the present study, we used a multi-channel NIRS to measure neuronal activity in a macaque monkey who was trained to watch videos showing various circus animals performing acrobatic activities without fixing the head position of the monkey. Cortical activity from the occipital region was measured first by placing a probe comprising a 3 × 5 array of emitters and detectors (2 × 4 cm) on the area (area 17), and the robustness and stability of the results were confirmed across sessions. Cortical responses were then measured from the dorsofrontal region. The oxygenated hemoglobin signals increased in area 9 and decreased in area 8b in response to viewing the videos. The results suggest that these regions are involved in cognitive processing of visually presented stimuli. The monkey showed positive responsiveness to the stimuli from the affective standpoint, but its attentional response to them was an inhibitory one.